THE BULLYING PHENOMENON: DIFFERENCES BETWEEN BOYS AND GIRLS - Fernanda Silva; Denise Dascanio; Tânia Gracy Martins do Valle (Editora da Universidade de Santa Cruz do Sul, 2016)
The bullying phenomenon is characterized by aggression always unequal power and involves violence. This study aimed to identify the types of bullying (physical, verbal, psychological, material, virtual or sexual) more prevalent in this population and compare bullying among adolescent males and females. We used a questionnaire prepared by the researcher. Participants were 309 students, 142 males and 167 females, from 6th to 8th grade from two schools, one state and one municipal. These results show 27% of participants were involved in episodes of bullying and that the most prevalent type of bullying was verbal, being appointed for 92% of girls and 84% boys; followed by psychological, indicated by 70% of girls and 53% boys. Physical bullying, had 46% of female and 44% male reports, the material was mentioned by 27% of girls and 16% boys. On sexual bullying type was greatest difference between the sexes, suffered by 38% of girls and 16% boys. Only 13% of girls and 12% boys, mentioned suffer the virtual bullying. Corroborating research area, in this study the highest percentage of victims were female and different from the literature girls reported being verbally abused more for boys than for girls.